Differential involvement of feedback and feedforward control networks across disfluency types in adults who stutter: Evidence from resting state functional connectivity - Hannah P. Rowe; Saul A. Frankford; Jackie S. Kim; Jason A. Tourville; Alfonso Nieto-Castanon; Frank H. Guenther (PLoS ONE, 2025)
Purpose This study investigated the relationship between different disfluency types (i.e., repetitions, prolongations, and blocks) and resting state functional connectivity in the feedback (FB) and feedforward (FF) control networks in 20 adults who stutter. Methods Frequency of each disfluency type was coded in speech samples derived from the Stuttering Severity Instrument, and functional connectivity between brain regions of interest was derived from resting state functional magnetic resonance imaging scans. We used LASSO regressions to identify the connections that most strongly predicted each disfluency type. Results Both repetitions and prolongations were significantly associated with increased connectivity in left ventral motor cortex – right ventral premotor cortex, which is hypothesized to be involved in FB control of speech. In contrast, blocks were significantly associated with reduced connectivity in right anterior cerebellum – left ventral lateral thalamic nucleus and increased connectivity in left presupplementary motor area – left posterior inferior frontal sulcus, both of which are hypothesized to be involved in FF control of speech. Conclusion Our findings suggest that repetitions and prolongations may be associated with increased reliance on FB-based corrective mechanisms, whereas blocks may be associated with disrupted FF-based initiation mechanisms. These neural underpinnings may correspond to different challenges in terminating or initiating motor commands and underscore the nuanced neurobiological processes underlying speech disfluencies.